Improving the Quality of Vocational Learning through Merdeka Learning (Literature Review): Peningkatan Mutu Pembelajaran Vokasi melalui Merdeka Belajar (Tinjauan Literatur) - Sabaruddin; Arifin; Nurmala, Eka; Hartati, Diah Vitaloka; Sultan (SABIQ: Jurnal Sosial dan Bidang Pendidikan, 2024)
The government is committed to providing education to all parts of the country in order to enhance the quality of education for everyone. The independent curriculum, which focuses on independent learning at independent campuses, aims to improve the quality of learning in educational institutions, particularly vocational education. This approach is based on the students' abilities, thus enabling them to compete globally by providing the skills required in the business and industrial workforce. The Systematic Literature Review (SLR) method was used in this research, which involves a systematic sorting of scientific sources before determining which ones are suitable for the purpose of obtaining more objective and reliable results. The research findings demonstrate that the independent curriculum through independent learning - independent campuses approach can enhance the quality of learning, especially in vocational education institutions, where it is crucial to prepare students for real-life work.